Comparison of the Rotational Stability of Two Toric Intraocular Lenses in 1273 Consecutive Eyes - Lee, Bryan S; Chang, David F (Ophthalmology (Rochester, Minn.), 2018)
To compare the rotational stability of the 2 most commonly used toric intraocular lenses (TIOLs). Retrospective cohort study in a single private practice. The study included all patients receiving an Acrysof (n = 626) or Tecnis TIOL (n = 647) over an 18-month period from April 2015 to September 2016. Patients were only excluded if their surgery could not be performed using a digital marking system. All patients had cataract surgery performed in the same surgical center with a similar technique. A digital marking system with limbal vessel registration was used to record the axis of the TIOL at the conclusion of surgery. A dilated examination was performed either later on the day of surgery or the next morning, and the postoperative rotation of the 2 TIOL models was compared. Patients who required a return to the operating room for TIOL repositioning were examined to determine risk factors for reoperation and subsequent outcomes. The primary outcome measure was the percentage of eyes with TIOL rotation >5 and >10 degrees. The second main outcome was likelihood of requiring return to the operating room to reposition a rotated TIOL. The Acrysof TIOL was less likely to rotate postoperatively, with 91.9% of eyes rotated ≤5 degrees at the first postoperative check compared with 81.8% of Tecnis TIOL eyes (P < 0.0001). This difference persisted for rotation ≤10 degrees (97.8% Acrysof vs. 93.2% Tecnis, P = 0.0002) and ≤15 degrees (98.6% Acrysof vs. 96.4% Tecnis, P = 0.02). The mean rotation was 2.72 degrees (95% confidence interval 2.35-3.08 degrees) for Acrysof and 3.79 degrees (95% confidence interval 3.36-4.22 degrees) for Tecnis TIOLs (P < 0.05). The Tecnis TIOL showed a strong predisposition to rotate counterclockwise, unlike the Acrysof. More Tecnis TIOL patients required repositioning (3.1% vs. 1.6%), but this did not reach statistical significance (P = 0.10). Refractive outcomes were similar between the 2 groups. The Acrysof TIOL showed significantly greater rotational stability than the Tecnis TIOL.